A Pixel to Pixel Correspondence and Region of Interest in Stereo Vision Application - Hamzah, Rostam Affendi; A Aziz, Khairul Azha; M Shokri, Ahmad Sayuthi (2012)
This paper presents an analysis of stereo images for an application of stereo vision application. The correspondence process is to determine the difference of intensities of pixel between stereo images while the region of interest ROI works as a reference area to the stereo vision application. This region is a reference view of the stereo camera and stereo vision baseline is based on horizontal configuration. The block matching technique is briefly described with the performance of its output. The disparity mapping is generated by the algorithm with the reference to the left image coordinate. The algorithm uses Sum of Absolute Differences (SAD) which is developed using Matlab software. The rectification and block matching processes are also briefly described in this paper.